Association of Low Birth Weight Infants and Maternal Sociodemographic Status in Tuzla Canton during 1992–1995 War Period in Bosnia and Herzegovina - Fahrija Skokić; Dubravka Bačaj; Amela Selimović; Evlijana Hasanović; Selma Muratović; Amir Halilbašić (International Journal of Pediatrics)
Objectives. We examined association between incidence rate of low birth weight in liveborn infants and maternal sociodemographic status in Tuzla Canton during 1992–1995 war in Bosnia and Herzegovina. Methods. The present study covers a 22-year period (1988–2009), including the war period (1992–1995), and we retrospectively collected data on a total of 108 316 liveborn infants and their mothers from three different socioeconomic periods: before (1988–1991), during (1992–1995), and after the war (1996–2009). Association between incidence rate of low birth weight in liveborn infants and maternal sociodemographic status were determined for each study period. Results. There were 23 194 live births in the prewar, 18 302 during the war, and 66 820 in the postwar period. Among the liveborn infants born during the war, 1373 (7.5%) had birth weight of <2500 g, which is significantly more in comparison with 851 (3.6%) liveborn infants in this birth weight group born before and 1864 (2.8%) after the war. We found the number of examinations during pregnancy was 1.8 per pregnant woman in the war period, which was low in comparison with the number of examinations before (4.6 per pregnant woman) and after (7.1 per pregnant woman) the war (𝑃<.001 for both). Prewar perinatal mortality LBW infants of 6.2 per 1000 live births increased to 10.8 per 1000 live births during the war (𝑃<.001), but after the war, perinatal mortality LBW infants (5.2‰) and early neonatal mortality (2.4‰) decreased. Conclusions. We found statistically significant association between low-birth-weight and maternal sociodemographic status in Tuzla Canton during 1992–1995 war in Bosnia and Herzegovina.